The Therapeutic Challenge of Disseminated Bone Marrow Metastasis From HR-Positive HER2-Negative Breast Cancer: Case Report and Review of the Literature - Garufi, Giovanna; Carbognin, Luisa; Orlandi, Armando; Palazzo, Antonella; Tortora, Giampaolo; Bria, Emilio (Frontiers in Oncology, 2021)
The efficacy and safety of the combination of endocrine therapy (ET) and CDK4/6 inhibitors for patients with hormone receptor (HR)-positive HER2-negative metastatic breast cancer (BC) presenting with visceral crisis or life-threatening conditions represents a challenge for daily clinical practice. Indeed, the peculiarity of this clinical presentation (signs and symptoms of rapidly progressive disease) does not allow to include such patients in trial aiming to drugs’ approval. On the basis of the scientific evidence available so far, chemotherapy represents the standard of care according to guidelines, on the basis of the more rapid activity in comparison with ET alone. Besides, the combination of ET and CDK4/6 inhibitors have demonstrated in clinical trials to have clinically impactful activity in short time, thus suggesting as potential role in advanced tumors which require rapid response. Herein, we report the clinical history of a young woman with HR-positive HER2-negative metastatic BC and a pancytopenia due to carcinomatosis of the bone marrow receiving letrozole and leuprorelin plus the CDK4/6 inhibitor palbociclib, who significantly derived clinical benefit from treatment. Considering that these peculiar cases are excluded from clinical trials, the estimation of the magnitude of the benefit of the newer ET combination may potentially represent a practical question for large case series and real-world studies.